THE EFFECT OF POLITICAL CONNECTIONS, LEVERAGE, AND CAPITAL INTENSITY ON TAX AVOIDANCE - Agustin, Dhiva Setra (DIPONEGORO UNIVERSITY, 2024)
Tax serves as the largest contributor to state revenue, playing a crucial role in funding infrastructure development aimed at improving public welfare. The government continuously strives to maximize tax revenue as one of the primary sources of national financing. However, corporate management often engages in tax avoidance strategies to reduce their tax obligations. This study aims to analyze the effect of political connections, Leverage, and capital intensity on tax avoidance in banking sub-sector companies listed on the Indonesia Stock Exchange (IDX) during the period 2021–2023. The Effective Tax Rate (ETR) is used as a proxy to measure the level of corporate tax avoidance. Political connections are measured using the natural logarithm (Ln), Leverage is measured using the Debt to Equity Ratio (DER), and capital intensity is measured by the ratio of total assets to total sales. This study employs purposive sampling to select the research sample, resulting in 34 companies as the final sample. Data analysis was conducted using multiple linear regression with the assistance of IBM SPSS version 26. The results show that political connections have no significant effect on tax avoidance, while Leverage and capital intensity have a significant negative effect on tax avoidance.